The Effect of Obesity on the Improvement in Health State Outcomes following Minimally Invasive Transforaminal Interbody Fusion. (December 2016) - McAnany, Steven J.; Patterson, Diana C.; Overley, Samuel; Alicea, Daniel; Guzman, Javier; Qureshi, Sheeraz A.
Study Design: Observational study. Objective: Studies have shown a correlation between obesity and lumbar spine pathology, but also that obese patients have higher rates of complication following lumbar spine surgery. It is unknown if obese patients have clinical gains following lumbar spine surgery comparable to the gain of normal-weight patients. This study investigated the correlation of obesity and the delta change in outcomes in a single surgeon's cohort of normal-weight and obese patients undergoing minimally invasive (MIS) transforaminal lumbar interbody fusion (TLIF). Methods: A retrospective review was performed of a single surgeon's patients at an academic medical center who underwent MIS TLIF between July 2011 and December 2013. Statistical analyses included independent sample t test for continuous variables, Fisher exact test for categorical data, and repeated measures two-way analysis of variance to assess the interaction between obesity status and the change in Short-Form Health Survey 12 (SF-12) results. Results: Thirty-eight patients from a single institution were reviewed, and 19 had a body mass index greater than 30. The nonobese and obese postoperative SF-12 mental composite scores (MCS; 52.70 ± 2.50 versus 52.16 ± 1.91; p = 0.87) and physical composite scores (PCS; 45.56 ± 2.72 versus 41.03 ± 2.65; p = 0.24) did not show any significant differences. There was no significant interaction between obesity and change in SF-12 MCS ( F [1, 36] = 0.96, p = 0.33) or SF-12 PCS ( F [1, 36] = 0.74, p = 0.40) between the pre- and postoperative scores. There was a significant effect of obesity on SF-12 PCS scores ( F [1, 36] = 7.15, p = 0.01). Conclusions: Patients undergoing MIS TLIF sustain meaningful and significant gains in SF-12 MCS and PCS that is not impacted by their obesity status.